High methionyl–tRNA synthetase expression predicts poor prognosis in patients with breast cancer. Issue 12 (13th May 2020) - Jin, Qin; Liu, Gang; Wang, Biao; Li, Shubin; Ni, Kan; Wang, Chunyu; Ren, Jingyu; Zhang, Shu; Dai, Yanfeng
Abstract : Aims: Methionyl–tRNA synthetase (MARS) is known to play a critical role in initiating translation and protection against cellular damages in vivo. The aim of this study was to clarify the role of MARS in breast cancer (BC) progression. Methods: The expressions of MARS messenger RNA (mRNA) and protein in human BC tissues and adjacent non-cancerous tissues were detected by quantitative real-time PCR, western blot and immunohistochemistry. The prognostic potential of MARS in patients with BC was assessed by univariate and multivariate survival analyses. The association between the MARS expression and BC progression was further evaluated by the bioinformatics database of UALCAN, Gene Expression Profiling Interactive Analysis (GEPIA) and Gene Expression Database of Normal and Tumor Tissues (GENT). The role of MARS in the proliferation, migration and epithelial-to-mesenchymal transition (EMT) of human breast cancer cell line (MCF-7 cells) was investigated after siRNA transfection. Results: The expression level of MARS mRNA in the fresh BC tissues was significantly higher than that in the adjacent tissues. Immunohistochemistry showed that the expression level of MARS was closely associated with the clinicopathologial parameters of patients with BC, including the HER-2 status, Ki-67 status, molecular classification, tumour grade, N stage and tumour, node, metastasis (TNM) stage, and this finding was further confirmed by UALCAN database. The Kaplan-Meier analysis showed that high MARS expression and TNM stage were predictors of poor prognosis of patients with BC. The proliferation, migration and EMT capabilities of MCF-7 cells were significantly suppressed after MARS knockdown. An overview of UALCAN, GEPIA and GENT results suggested that MARS may be an oncogene of BC, as well as a potential therapeutic target of this malignant tumour. Conclusions: High expression level of MARS in the human BC tissues was significantly associated with the unfavourable prognosis of patients with BC, suggesting that MARS may serve as a potential prognostic marker for the clinical diagnosis and prognostic prediction of BC.